How are quadratic equations solved ? Please explain with the example: u^2 + 6u = 27.
- print Print
- list Cite
Expert Answers
calendarEducator since 2010
write12,544 answers
starTop subjects are Math, Science, and Business
We have to solve the equation u^2 + 6u = 27.
First bring all the terms to one side
=> u^2 + 6u - 27 = 0
One method of finding the roots which works when the roots are integers or fractions is to split the coefficient of u into two parts which add up to 6 and the product of which is -27. We can achieve this with 9 and -3.
=> u^2 + 9u - 3u - 27 = 0
remove the common factors of the first two terms and the last two terms.
=> u(u + 9) - 3(u + 9)
factorize again
=>(u - 3)(u + 9) = 0
u - 3 = 0 => u = 3
and u + 9 = 0 => u = -9
This gives us the roots of the equation as 3 and -9.
Related Questions
- Solve the equation x^2 - 6x + 5 = 0 use the quadratic formula and factorization.
- 2 Educator Answers
- Solve the equation: |3x+2|=|3-2x|Solve the equation: |3x+2|=|3-2x|
- 1 Educator Answer
- how does making of a roller coaster require quadratics math? with an equation example?
- 1 Educator Answer
- Given y=f(u) and u=g(x) find dy/dx=f'(g(x))g'(x) y=6u-9, u=(1/2)x^4I have reread this chapter....
- 1 Educator Answer
- solve the equation: 2^(2x-1)= 8^x
- 1 Educator Answer
calendarEducator since 2008
write3,662 answers
starTop subjects are Math, Science, and Social Sciences
Given the quadratic equation:
u^2 + 6u = 27
We need to solve for u.
First we will rewrite into the standard form.
==> u^2 + 6u - 27 = 0
Now we will factor the equation.
==> (u+9)(u-3) = 0
Now we will solve.
==> u1= -9 and u2= 3
Then, we have two solutions for the quadratic equations.
==> -9 and 3 are the roots for the equation.
Unlock This Answer Now
Start your 48-hour free trial to unlock this answer and thousands more. Enjoy eNotes ad-free and cancel anytime.